Economic Participation among Older People: Key Influencing Factors and Social Work Practice Implications (Journal of Comparative Social Work, 2025)
Economic participation studies often emphasize challenges of accessing and engaging in formal employment after retirement. However, they tend to overlook personal factors, traditional values, and culturally specific elements in rural settings that influence participation in informal work. This study explored the factors that influence older people’s participation in handcraft activities in the Masasi District in Tanzania. It provides a deeper insight into their continued engagement, and highlights its implications for social work practice.This study explored the factors that influence the participation of older people in handcraft activities to provide a deeper insight into their continued engagement and its implications on social work practice. A phenomenology method was used, and in-depth interviews were employed to collect data from purposively sampled older people working in handcraft through the lens of decolonial theory. The analysis revealed that older people’s participation in handcraft activities was triggered by poor living conditions, the need for income to meet essential needs, a lack of formal and inadequate informal support, parenting and grand-parenting obligations, as well as the desire to maintain personal agency and avoid dependence syndrome.The findings suggest that the traditional role of extended family and community, as a pillar of care and protection of older people, should be enhanced to improve their working lives and well- being. Older people working in handcraft activities should be empowered in their socio- economic issues to improve their working and quality of life in rural communities. Collaboration between social workers and the community at the grassroots level is crucial, and social work knowledge and practice that reflect and promote indigenous knowledge and practices should be developed and adopted.